The potency of Soft Coral Sarcophyton in Krakatau Seas as Cytotoxic Test - Tri Nur Sujatmiko; Tio Dwi Wibisono; Ariefianto Tri Mahadi; Paradita Hasanah; Hedi Indra Januar; Neviaty Putri Zamani (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2019)
Soft coral is one of the marine organisms that produce secondary metabolites materials and has potency as anticancer. There is much research to find bioactive compounds in the organism, but it still lacks data to find potency of bioactive in soft coral that lives under acidification pressure. The objectives of this study are to determine the characteristic of acidification in Krakatau seas and to assess the potency of cytotoxic activity from soft coral Sarcophyton. Sampling was conducted in three locations, Legon Tuo, Legon Cabe, and Umang-umang Island, to take the sample and measure water quality. Cytotoxic test using MTT method (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolinon) to MCF-7 cancer cell line to measure growth inhibition percentage. Data were analyzed using ANOVA, post hoc analysis, and multivariate analysis. Water quality in Legon Tuo and Legon Cabe have significant different to Umang-umang Island. However, Legon Tuo and Legon Cabe are suitable as acidification site, while Umang-umang Island as the reference site. The characteristic of Krakatau seas, especially in Legon Tuo and Legon Cabe study site, was categorized in low acidification. In the cytotoxic activity, soft coral Sarcophyton from Legon Cabe (acidification site) is more potential than soft coral from Umang-umang Island (reference site).